The power of a positive no : how to say no and still get to yes - Ury, William (New York : Bantam Books, 2008)
Describes the art of the "Positive No," a three-step method for saying "no" to people at work, home, and in the community without destroying relationships.
Includes bibliographical references and index.
Library Journal Starred.
Publisher's Weekly.
Adult
Keywords: Negotiation; Negotiation